2021
DOI: 10.1007/s10854-021-06276-9
|View full text |Cite
|
Sign up to set email alerts
|

Au–Ag binary alloys on n-GaAs substrates and effect of work functions on Schottky barrier height

Abstract: In this study, I investigated the effect of work function (ϕm) of AuxAg1-x (x=0, 0.22, 0.37, 0.71 and 1) on the Au-Ag/n-GaAs Schottky diode (SD) parameters. Ag, Au and three alloys with different compositions deposited on n-GaAs substrates by thermal evaporation method. Surface morphologies of the samples were investigated by atomic force microscope (AFM). Elementel compositions of Schottky metals were conducted by the energy dispersive X-ray spectroscop (EDX). Current-voltage (I-V) and capacitance-voltage (C-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 72 publications
0
3
0
1
Order By: Relevance
“…Work function ( W F ) [ 36 ] can be expressed as W F = E 0 ‐ E F , where E 0 is the electrostatic potential of vacuum, and E F is the Fermi level. The calculated work functions of Au, MoS 2 , and Au/LiF are 5.29, 5.87, 5.25 eV, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Work function ( W F ) [ 36 ] can be expressed as W F = E 0 ‐ E F , where E 0 is the electrostatic potential of vacuum, and E F is the Fermi level. The calculated work functions of Au, MoS 2 , and Au/LiF are 5.29, 5.87, 5.25 eV, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Where 𝜌 MoS2 , 𝜌 Au , 𝜌 Au∕MoS2 , 𝜌 Au∕LiF∕MoS2 , and, 𝜌 LiF are the plane average charge densities of MoS 2 , Au, Au/MoS 2 , Au/LiF/MoS 2 , and LiF, respectively. Work function (W F ) [36] can be expressed as have the electrostatic potential difference of 3.3 eV with intercalated LiF (monolayer), implying a change of the electrostatic field between the interfacial layers.…”
Section: Interface Contact and Electronic Properties Of Au/mos 2 And ...mentioning
confidence: 99%
“…Hatta metal ve yarıiletken birleştiğinde oluşan ara yüz bileşiminin engel yüksekliği üzerinde etkisi ara yüzey yapısından daha etkili olduğu bildirilmektedir (Aboelfotoh, 1987). Belirli bir amaca hizmet edecek diyotların üretimi sırasında diyot parametrelerinin belirlenmesi için farklı iş fonksiyonlarına sahip metallerin veya yarıiletkenlerin kullanılması genellikle yeterlidir (Abdullah Akkaya, 2021;Myburg, Auret, Meyer, Louw, & Van Staden, 1998). İş fonksiyonu, malzeme yüzeylerinin en temel özelliklerinden biridir ve metalyarıiletken kontakların elektriksel özelliklerini doğrudan etkilemektedir (Ishii, Matsumura, Sakai, & Sakata, 2001) Üretilen bir devre elemanının tam kapasite ile çalışabilmesi, devreyi oluşturan temel yapının, bütün özelliklerinin bilinmesine bağlıdır.…”
Section: Introductionunclassified
“…19 Specifically, surface defects can increase the effective Schottky barrier height (SBH, Φ B ) by causing surface Fermi level pinning. 19,20 Thus, surface treatment was performed to alleviate the surface state-induced characteristic of semiconductors. 19 It was found that for InGaP/InGaAs/Ge triple-junction solar cells, the treatment of the AlInP window layer with (NH 4 ) 2 S x solution resulted in about 3% increase in the conversion efficiency.…”
mentioning
confidence: 99%